2011
DOI: 10.1061/(asce)hy.1943-7900.0000396
|View full text |Cite
|
Sign up to set email alerts
|

Near-Bed Turbulence Characteristics at the Entrainment Threshold of Sediment Beds

Abstract: This experimental study is devoted to quantification of the near-bed turbulence characteristics at an entrainment threshold of noncohesive sediments. Near the bed, the departure in the distributions of the observed time-averaged streamwise velocity from the logarithmic law is more for immobile beds than for entrainment-threshold beds. In the Reynolds shear stress distributions, a damping that occurs near the bed for sediment entrainment is higher than that for immobile beds. Quadrant analysis reveals that in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 45 publications
(45 reference statements)
3
33
0
Order By: Relevance
“…Similar conclusions can be found in Dey et al (2011b), however earlier observations by Heathershaw 56 and Thorne (1985) revealed that outward interactions, although weaker and less frequent than 57 sweeps, are still capable of causing sediment movement at intermediate (i.e., not extreme) values of 58 the local velocity fluctuations. 59…”
Section: Introduction 24supporting
confidence: 81%
“…Similar conclusions can be found in Dey et al (2011b), however earlier observations by Heathershaw 56 and Thorne (1985) revealed that outward interactions, although weaker and less frequent than 57 sweeps, are still capable of causing sediment movement at intermediate (i.e., not extreme) values of 58 the local velocity fluctuations. 59…”
Section: Introduction 24supporting
confidence: 81%
“…A number of studies highlighted some key differences between fixed bed and movable bed hydraulics in steady open channel flow (Graf 1971, Nikora andGoring 2000). Some results implied a greater turbulence anisotopy in presence of mobile bed (Nikora and Goring 2000) with a damping of near bed turbulence (Dey et al 2011). To date, however, no systematic study was performed in highly unsteady open channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these parameters are of second order only. Third-order parameters like TKE flux in stream-wise and vertical direction were discussed in literatures (Bey et al 2007;Dey et al 2011;Krogstadt and Antonia 1999;Wang et al 2012). Turbulent diffusion, a third-order parameter, was also mentioned in several turbulence researches (da Silva et al 2014;Elder 1959;Jones and Whitelaw 1982;McComb 1990;Reeks 2014;Taylor 1954).…”
Section: Parameters and Methodsmentioning
confidence: 99%